Dekonstruksi Semiotika Wayang Semar: Implementasi Pola Geo-Construction dalam Busana Avant Garde - Yuniarti, Novi; Fadlia, Adlien (Jurnal SeniRupa Warna, 2026)
This research explores the transformation of the philosophical meaning of the Semar puppet character into an Avant-Garde fashion strategy through a qualitative approach method referring to library research by collecting data from books, journals and documentation related to the Semar puppet and applying the J.I.W.A.A. artistic creation method. (Exploration, Intuition, Form, Authentic, Adiluhung The main problem of the research focuses on the challenge of integrating the Javanese cosmological concept of the relationship between the Microcosm (Jagad Alit) and the Macrocosm (Jagad Ageng) into experimental fashion aesthetics. Wayang Semar is interpreted as a hybrid figure, namely a down-to-earth god or the personification of the union of heaven and earth. The technical challenge lies in the deconstruction of Semar's round and organic physical characteristics into an asymmetrical Avant-Garde fashion visual, and not without conventionally reducing its philosophical essence. This research method uses a semiotic approach and Geo-construction pattern development techniques. The Exploration stage is carried out through visual observation of Semar's signs, followed by the Intuition phase in the form of contemplation of the spiritual value of protection that triggers the imagination of geometric forms. In the Form stage, the Geo-construction structure transforms the organic body into a magnificent local three-dimensional volume precision pattern. The final stage, Adiluhung, represents the achievement of experimental aesthetics that contain the noble values ​​of tradition. The results of the study show that architecture is able to represent the depth of Semar's philosophical narrative into the silhouette of fashion Contemporary. This synergy between wayang tradition and modern techniques demonstrates that deconstructing cultural symbols can be a creative strategy for fostering discourse on sustainable fashion art, which has been marginalized by local identities in a global context.